Mammographic Evaluation of Breast Mass & Comparison with Histopathological Findings - Yesmin, Lovely; Hossain, Rued; Haldar, Bibekananda; Hossain, Mohammad Sazzad; Nahid, Sajida; Saiham, Kazi Shantono; Jahan, Nusrat (Journal of Current and Advance Medical Research, 2018)
Background: Mammography is used for the detection of breast cancer. Objective: The purpose of the present study was to evaluate the diagnostic performance of Mammography in the diagnosis of benign and malignant breast mass. Methodology: This cross-sectional type of study was carried out in the Radiology & Imaging department of Sir Salimullah Medical College and Mitford Hospital, Dhaka, during July 2013 to June 2015. Patients clinically suspected as having breast mass, referred in the above mentioned hospitals and enrolled for surgical management were included in this study. Mammography were done in all these patients and they were followed up from the admission up to the post-operative tissue diagnosis of breast mass in respective pathology departments for histopathological correlation. Results: A total of 41 patients had mass among them, 3(7.3%) cases were malignant and 38(92.7%) cases were benign patients. Histopathological diagnosis of invasive ductal carcinoma, invasive lobular carcinoma and medullary carcinoma were 8(14. %), 4(7.00%) and 1(1.8%) respectively. Mammography malignant was found 14 cases out of which 10(76.9%) malignant and 4(9.1%) benign evaluated by histopathology. Mammography benign was found 43 cases out of which 3(23.1%) malignant and 40(90.9%) benign evaluated by histopathology. The sensitivity was 76.9%, specificity 90.9%, accuracy 87.7%, positive predictive values 71.4% and negative predictive values 93.0% in mammography. Conclusion: Mammography is highly sensitive, specific, reliable and useful method in the differentiation of malignant and benign breast masses. Journal of Current and Advance Medical Research 2017;4(2):53-57